Pulmonary complications in neurosurgical patients - Randeep Guleria; Karan Madan (Indian Journal of Neurosurgery)
Pulmonary complications are a major cause of morbidity and mortality in neurosurgical patients. The common pulmonary complications in neurosurgical patients include pneumonia, postoperative atelectasis, respiratory failure, pulmonary embolism, and neurogenic pulmonary edema. Postoperative lung expansion strategies have been shown to be useful in prevention of the postoperative complications in surgical patients. Low tidal volume ventilation should be used in patients who develop acute respiratory distress syndrome. An antibiotic use policy should be put in practice depending on the local patterns of antimicrobial resistance in the hospital. Thromboprophylactic strategies should be used in nonambulatory patients. Meticulous attention should be paid to infection control with a special emphasis on hand-washing practices. Prevention and timely management of these complications can help to decrease the morbidity and mortality associated with pulmonary complications.